OPTIMIZATION OF STUDENT MANAGEMENT IN ENHANCING THE BRAND IMAGE OF MADRASAH - Kamal Izzuddin; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study examines the optimization of student management in enhancing the brand image of madrasah through a library research approach. It aims to describe and analyze the planning, organizing, actuating, and controlling of student management that contribute to the improvement of the madrasah's image. Data were collected through documentation of primary literature (scholarly journals published 2020–2025) and secondary literature (textbooks published 2015–2025 and education policy documents), then analyzed using the content analysis technique of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing and verification. The findings indicate that: (1) effective planning involves collective discussion, a focus on service quality and student admission, and continuous evaluation; (2) organizing is carried out according to job descriptions, cultivates a problem-solving discussion culture, and builds external cooperation; (3) actuating includes providing direction, role modelling, and support for teaching staff's professional development; (4) controlling is conducted through academic supervision using standardized instruments accompanied by constructive feedback. The study concludes that the systematic and integrated optimization of the four student management functions contributes significantly to strengthening the madrasah's brand image.